(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The research aims to show the importance of applying Financial Reporting Standard No. 8 accounting policies and changes in accounting estimates and errors to achieve tax justice for taxpayers and the General Tax Authority, because of the importance of the standard because it contains the principles and foundations that must be taken into account when preparing financial statements to give them more credibility, appropriate, where the research problem was the emergence of many problems, and obstacles in addressing changes in policies, estimates, and accounting errors as a result of rapid changes and developments in the business world, so it was formulated International Accounting Standard (IAS8) Accounting policies and changes in accounting estimates and errors to address these problems, and as a result, the question arose whether there is an impact of the application of International Accounting Standard No. (8) on net income and its reflection on tax justice, and the deductive approach (from general to private) was adopted in covering the theoretical side of the research, while the practical side is the inductive approach by linking the research variables and adopting financial data and reports for the research sample companies.